2004
DOI: 10.1051/0004-6361:20035778
|View full text |Cite
|
Sign up to set email alerts
|

The cellular burning regime in type Ia supernova explosions

Abstract: Abstract. We investigate the interaction of thermonuclear flames in Type Ia supernova explosions with vortical flows by means of numerical simulations. In our study, we focus on small scales, where the flame propagation is no longer dominated by the turbulent cascade originating from large-scale effects. Here, the flame propagation proceeds in the cellular burning regime, resulting from a balance between the Landau-Darrieus instability and its nonlinear stabilization. The interaction of a cellularly stabilized… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Although the most satisfactory approach to the problem would be to reveal the mechanism from first physical principles, this is an exceedingly difficult task in view of the many different length and temporal scales involved and of the huge diversity of initial conditions that can be imagined. Even though some advances have been brought about (Khokhlov 1991;Khokhlov et al 1997;Niemeyer & Woosley 1997;Niemeyer 1999;Lisewski et al 2000;Röpke et al 2004;Zingale & Dursi 2007) no sound mechanism for the transition has yet been found. Given the lack of a consistent physical picture of the DDT mechanism the opposite path is usually taken, trying to constrain the conditions of DDT by comparing the resulting explosion with the observational data of SNIa.…”
Section: Discussionmentioning
confidence: 99%
“…Although the most satisfactory approach to the problem would be to reveal the mechanism from first physical principles, this is an exceedingly difficult task in view of the many different length and temporal scales involved and of the huge diversity of initial conditions that can be imagined. Even though some advances have been brought about (Khokhlov 1991;Khokhlov et al 1997;Niemeyer & Woosley 1997;Niemeyer 1999;Lisewski et al 2000;Röpke et al 2004;Zingale & Dursi 2007) no sound mechanism for the transition has yet been found. Given the lack of a consistent physical picture of the DDT mechanism the opposite path is usually taken, trying to constrain the conditions of DDT by comparing the resulting explosion with the observational data of SNIa.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of flames interacting with turbulence have focused on flames interacting with vortical flow (see the twodimensional simulations presented in Röpke et al 2004) or statistical methods using one-dimensional turbulence ( Lisewski et al 2000a( Lisewski et al , 2000b). An open question is whether in the distributed burning regime a mixed region of partially burned fuel and ash can grow large enough that it can ignite a detonation ( Niemeyer & Woosley 1997;Khokhlov et al 1997;Niemeyer 1999).…”
Section: à3mentioning
confidence: 99%
“…For example, Im et al mention a quadratic dependence on the turbulence velocity in the case of weak turbulence [34]. On the other hand, Röpke et al report a linear relation even for turbulence velocities which are only marginally larger than the laminar flame speed in two-dimensional numerical simulations [35]. However, this result is possibly unsubstantial for the three-dimensional case.…”
Section: The Turbulent Flame Speed Relationmentioning
confidence: 99%
“…Hence, the corresponding spatial averages in equation (35) will not be sufficiently well behaved at the beginning. Although, the dynamics is dominated by the fuel domain at this point, both the enumerator and dominator in equation (35) are smoothed in time via convolution with an exponential damping function in order to remove strong oscillations in the ash and flame regions. The characteristic time scale of smoothing is prescribed by the parameter T .…”
Section: The Semi-localized Modelmentioning
confidence: 99%